The Impact of Accident Experience on Unsafe Behaviors of Construction Workers Within Social Cognitive Theory - Su Yang; Lingyu Liu; Ting Wang; Yongqi Guo; Yingmiao Qian; Huihua Chen (Buildings)
The construction industry’s poor safety is a global issue, with construction workers’ unsafe behaviors (CWUBs) identified as a major cause of accidents. Based on social cognitive theory (SCT) and using multiple regression analysis, this study categorizes accident experience (AE) into direct and indirect types, examining how each affects CWUBs and the roles of risk perception (RP), safety attitude (SA), and safety competence (SC) in these relationships. Utilizing a structured questionnaire completed by 334 valid respondents and analyzed through structural equation modeling (SEM), the study found that indirect experience (IE) significantly reduced CWUBs, with a standardized path coefficient of −0.364, while direct experience (DE) has a smaller impact, with a standardized path coefficient of −0.154, but a significant p. Furthermore, IE positively influenced RP, SA, and SC, explaining 66.8% of its total effect. This study offers a new framework for understanding how AE influences CWUBs, providing actionable insights for managers to implement effective strategies that reduce CWUBs on construction sites.